Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 8. Beitrag. Diptera: Nycteribiidae und Streblidae. - Hůrka, Karel (Contributions to Entomology = Beiträge zur Entomologie, 1963)
Apart from a study of the family Nycteribiidae after material collected by the expedition of the Deutsches Entomologisches Institut to Albania (including 5 species) there is given a complete review of the Nycteribiidae hither to known from this country (7 species) and 1 species of the family Streblidae.